Analysing the Screenplay. - Nelmes, Jill (Taylor & Francis, 2010)
Most producers and directors acknowledge the crucial role of the screenplay, yet the film script has received little academic attention until recently, even though the screenplay has been in existence since the end of the 19th century. "Analysing the Screenplay" highlights the screenplay as an important form in itself, as opposed to merely being the first stage of the production process. It explores a number of possible approaches to studying the screenplay, considering the depth and breadth of the subject area, including: the history and early development of the screenplay in the Un.